The 3‐D geological model around Chang'E‐3 landing site based on lunar penetrating radar Channel 1 data. Issue 13 (8th July 2017) - Yuan, Yuefeng; Zhu, Peimin; Zhao, Na; Xiao, Long; Garnero, Edward; Xiao, Zhiyong; Zhao, Jiannan; Qiao, Le
Abstract: High‐frequency lunar penetrating radar (LPR) data from an instrument on the lunar rover Yutu, from the Chang'E‐3 (CE‐3) robotic lander, were used to build a three‐dimensional (3‐D) geological model of the lunar subsurface structure. The CE‐3 landing site is in the northern Mare Imbrium. More than five significant reflection horizons are evident in the LPR profile, which we interpret as different period lava flow sequences deposited on the lunar surface. The most probable directions of these flows were inferred from layer depths, thicknesses, and other geological information. Moreover, the apparent Imbrian paleoregolith homogeneity in the profile supports the suggestion of a quiescent period of lunar surface evolution. Similar subsurface structures are found at the NASA Apollo landing sites, indicating that the cause and time of formation of the imaged phenomena may be similar between the two distant regions. Key Points: A 3‐D geological model with lava flow directions near the Chang'E‐3 landing site is presented The homogeneity of Imbrian paleoregolith supports a lunar quiescence period Imaged subsurface structures are similar to those found at Apollo landing sites